Development, programming and start-up of an interchangeable 3D-printing module - Oliveira, Hugo Miguel Lopes de (2017)
This report has as main objective the development and application of a 3D printing module (additive manufacturing) in a computer numeric control (CNC) milling machine (subtractive manufacturing) creating a hybrid manufacturing environment that could offer the advantages of both methods. Every CNC milling machine using this 3D printing module could be converted in a 3D printer by changing from a regular tool to the 3D printing module which is applied in the spindle of the machine in a very simple process. This module is equipped with a system capable of reading the spindle rotation speed, and uses that information to set up different commands and actions. Focused in the development of a low-cost system, there is used an Arduino board to control all the systems needed to work with the module. Most of the parts of the module are printed in a 3D printer that uses the stereolithograph technology, being able to create parts with complex shapes, high precision and good surface finishing. The experimental results obtained in the first tests were not as expected. Many problems that haven’t been taken in consideration when the initial development of the module was done. Many solutions were found and some corrections were done to eliminate or minimize those problems. The temperature control system and the revolutions per minute reading system shown very good results in the experimental tests. The biggest issue faced was related with filament feeding system. Many structural modifications were implemented to improve it, with better performance, obtaining acceptable final results, however with significant possibilities for improvement.